Educational Evaluation of Relapse Using Choreographic Video Media on the Utilization of IPWL - Sherly Shobur (International Journal Scientific and Professional (IJ-ChiProf), 2022)
The key to preventing addict relapse is understanding that relapse occurs gradually. In providing an understanding, it is necessary to provide education to the families of drug addicts. One of the media that can be used is choreography video. The use of choreographic video media as an educational medium is one of the efforts that can be made by the government in preventing relapse for drug users through the Compulsory Report Receiving Institution (IPWL). Education is needed to increase knowledge and understanding of families about relapse. This study aims to describe the design and rationale of a randomized controlled trial evaluating the effect of relapse education using choreographic video media on the use of IPWL in a population of drug addicts. Methods: This study used a mixed method design with an embedded type of sequential explanatory experimental model. Respondents are families of drug addicts. The data collected includes knowledge about recurrence, patterns of prevention, and handling when relapses occur and evaluation of relapses. Results: Study of evaluation of relapse education using choreography video media on the use of IPWL. This study will determine whether the relapse education program using choreography video media can be used as an effort to prevent relapse in certain populations. If proven effective, the program has the potential to be scaled up, adapted and implemented in other special populations.